2019
DOI: 10.1016/j.bbr.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Adult social isolation leads to anxiety and spatial memory impairment: Brain activity pattern of COx and c-Fos

Abstract: Social isolation during adulthood is a frequent problem that leads to a large variety of adverse emotional and cognitive effects. However, most of the social isolation rodent procedures begin the separation early post-weaning. This work explores locomotor activity, anxiety-like behaviour, and spatial working memory after twelve weeks of adult social isolation. In order to study the functional contribution of selected brain areas following a working memory task, we assessed neuronal metabolic activity through q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 77 publications
2
32
0
1
Order By: Relevance
“…Prolonged single-housing in rats (not mice) is considered as a social isolation stress model that causes activation HPA axis, and it has been used to model signs and symptoms of mental disorders and neurological conditions such as anxiety, depression, schizophrenia, epilepsy and memory loss [73]. In particular, our research group has recently reported anxiety-like behavior, impaired working memory, and altered brain CCO activity in adult rats after 12 weeks of single-housing, as compared with rats reared in groups of 4 [74].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged single-housing in rats (not mice) is considered as a social isolation stress model that causes activation HPA axis, and it has been used to model signs and symptoms of mental disorders and neurological conditions such as anxiety, depression, schizophrenia, epilepsy and memory loss [73]. In particular, our research group has recently reported anxiety-like behavior, impaired working memory, and altered brain CCO activity in adult rats after 12 weeks of single-housing, as compared with rats reared in groups of 4 [74].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that our animals were housed individually following MCAO due to concerns that housing the animals in pairs would be dangerous due to the wounds present, and concerns regarding poststroke feeding competition and recovery. We consider this to be one of the limitations of our study as social isolation is known to be an influencing factor on animal behavior in cognitive tests 38 . However, the differences in behavior we found between the experimental groups were all among animals of the same housing conditions, leading to our conclusion that the behavioral differences observed were a result of strain differences rather than the housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies conducted to examine the effect of housing environment on behavior, and their results indicate that long‐term social isolation housing induces social stress in laboratory animals and increases emotional behavioral changes (Brenes et al., 2008; Oliveira et al., 2019; Skelly et al., 2015; Zorzo et al., 2019). Many previous studies have reported that rats kept in social isolation show an increase in depressive‐like behavior or anxiety‐like behavior, and a decrease in social contact compared to rats kept in a group (reviewed in Arakawa, 2018; Burke et al., 2017; Robbins, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the most significant effects of rearing rats in isolation are reported to occur during weaning to early adulthood, which is a critical phase (Arakawa, 2005; Ferdman, Murmu, Bock, Braun, & Leshem, 2007). In addition, recent studies have reported that various emotional and behavioral changes occur as a result of social isolation, including an increase in aggressiveness (Krupina, Khlebnikova, Narkevich, Naplekova, & Kudrin, 2020), anxiety‐like behavior (Zorzo, Méndez‐López, Méndez, & Arias, 2019), and social interactive behavior (Kambali, Anshu, Kutty, Muddashetty, & Laxmi, 2019).…”
Section: Introductionmentioning
confidence: 99%